Analisis Semiotika Desain Poster Iklan Layanan Masyarakat di Instagram Polres Labuhan Batu Edisi Stop Pembakaran Hutan - Ardiansyah, Yogie; Harahap, Muhammad Said (Universitas Muhammadiyah Sumatera Utara, 2025)
Forest fires can be interpreted as one of the problems that is often faced by every region, including the Labuhan Batu area. Therefore, the local government and the Labuhan Batu district police created a program by forming a team of operators to stop forest and land fires. By making public service advertisement posters made by the Labuhan Batu Police and uploading them on social media such as Instagram with the aim of advertising that invites the public to start protecting and preserving the forest ecosystem in Labuhan Batu. This research aims to find out what meaning is contained in the public service advertisement poster edition of stop forest burning, as well as knowing the signs, objects, interpretants in the poster. The method used in this research is qualitative. The researcher used a descriptive qualitative approach and used text research techniques, namely semiotic analysis using Charles Sanders Peirce's analysis techniques on public service advertisement posters for the stop forest burning edition. Researchers use qualitative data collection techniques, namely using documentation and observation techniques. By using primary and secondary data analysis. The results of this research show that the design of the public service advertisement poster published on the Instagram of the Labuhan Batu police station can be found in accordance with Charles Sanders Pierce's semiotic analysis, with the sign explaining that there is a picture of a natural disaster, namely a forest fire, which is depicted with raging fire so that part of the forest is on fire and there are also officers extinguishing the fire. The object is the flames on the public service advertisement poster which means danger and also contains an appeal that says